Building a Solidarity Economy in the 21st Century - Lewis, Mike; Conaty, Patrick (Newsletter of the North American Network for the Solidarity Economy, 2004)
"If we don't set out a stronger theoretical base for our work, if the movements we build are simply pragmatic & without a sound intellectual base, we will not succeed in changing hearts and minds." Pat Conaty
Keywords: solidarity economy